Isu-Isu Kontemporer Pendidikan Agama Islam Di Era Digitalisasi - Masruroh, Emi; Khoiroh, Wus’atul (IAIN Datuk Laksemana Bengkalis, Indonesia, 2025)
The aim of this article is to analyze contemporary issues of Islamic religious education in the era of digitalization. The research method used is a literature review. The research results show that contemporary issues of Islamic religious education in the era of digitalization include transformation of learning methods, access and equality, quality of materials, character and ethics formation, curriculum integration. The implication of the research is that a more interactive and flexible teaching approach needs to be implemented, where students can learn independently and collaborate through technology. The government and educational institutions must ensure the affordability of technological devices, as well as provide subsidy programs or technology assistance for underprivileged students so that there is no inequality in access to education. Islamic religious education materials must be adapted to current developments without ignoring essential religious values. Then technology must be used as a tool to instill Islamic character values, such as honesty, responsibility and discipline, both in the virtual and real world. Learning must be more adaptive to technological developments, but still prioritize Islamic faith and law.